Low-molecular-weight dextran-induced anaphylactic shock immediately after intracoronary imaging. Issue 3 (September 2022) - Dai, Kazuoki; Oi, Kuniomi; Hyodo, Yohei; Jyuri, Yusuke; Takayama, Shin; Shigehara, Mikio; Tomomori, Shunsuke; Higaki, Tadanao; Kawase, Tomoharu; Suenari, Kazuyoshi; Nishioka, Kenji; Otsuka, Masaya; et al.
Abstract: Dextran has been frequently used during intracoronary imaging, such as in optical coherence tomography, optical frequent domain imaging, and coronary angioscopy. We report a case of dextran-induced anaphylaxis in a 70-year-old male with chronic coronary disease. Upon admission, we performed coronary angiography and coronary angioscopy on the patient. After the intracoronary imaging, the patient's blood pressure suddenly fell to 50 mmHg and a rash appeared on his chest. The patient was diagnosed as having dextran-induced anaphylactic shock. Epinephrine was administered repeatedly, and his blood pressure gradually recovered after administering a total of 6 mg epinephrine. There was no recurrence of the anaphylactic shock, and the patient was discharged 12 days later. The incidence of dextran-induced anaphylactic reactions is extremely low; however, they can be fatal. The possibility of anaphylactic shock induced by dextran should be kept in mind by all cardiovascular interventionalists performing intracoronary imaging. Learning objective: Dextran has been frequently used during intracoronary imaging. We report on a case of dextran-induced anaphylaxis in a 70-year-old male with chronic coronary disease. While the incidence of dextran-induced anaphylactic reactions is extremely low, it can lead to fatal events. The possibility of anaphylactic shock induced by dextran should be kept in mind by all cardiovascular interventionalists while performing intracoronary imaging.